From research to classroom: A narrative review of assistive technology forlow-functioning pupils - Salleh, Rosmalily; Rajaratnam, Vaikunthan (Jurnal Pendidikan Bitara UPSI, 2025)
Assistive technology (AT) is increasingly recognised as a powerful enabler of inclusion for pupils with complex intellectual, motor, and communicative disabilities. Yet, practical guidance for its effective use in classrooms remains limited. This narrative review synthesises evidence from 33 studies involving approximately 1,100 pupils (median sample size = 10; intervention durations up to 12 weeks) identified through an AI-assisted systematic search. Two researchers independently screened, appraised, and cross-verified all eligible studies. Across diverse contexts, tools such as eye-gaze systems, speech-generating devices, tablet applications, and speech-to-text software consistently improved expressive communication, early literacy and numeracy, and on-task classroom behaviour—provided they were tailored to individual needs, embedded in explicit teaching routines, and supported by sustained teacher coaching. Without these supports, even advanced technologies produced minimal gains. Beyond academics, AT often enhanced learner agency and peer interaction, suggesting wider psychosocial benefits. These findings highlight the need for ongoing teacher professional development, careful device customisation, and seamless integration of AT into daily learning activities. While the small scale and short duration of most studies limit certainty, the evidence underscores that implementation quality matters more than the novelty of the device. Future large-scale, long-term studies should examine cost-effectiveness and participation outcomes to guide equitable, scalable AT adoption in mainstream education.